Status of Participation in Physical Activity by Employees in Kenyan Universities at Onsite Fitness Centers in Kenya - Matilda , Mukaro; Kamau , Jayne W.; Mwangi , Francis M.; Wanderi , M. P.; Onyango , Elvis O. (African Journal of Education,Science and Technology (AJEST), 2020)
Physical activity plays a critical role in preventing and reducing risks of many diseases while at the same time maintaining physical and mental health. On the contrary, physical inactivity has been found to be one of the four modifiable risk factors that potentially predispose individuals to Non-communicable diseases (NCDs). To curb the negative social and financial implications associated with NCDs, many corporate organizations, as well as universities, are offering furnished wellness centers to their employees. This paper is based on a study that aimed at establishing the status of participation in physical activity (PA) at onsite fitness centers among Kenyan university employees. A cross-sectional analytical design was used to examine 499 employees from two institutions (a private and public university) that were purposefully selected on the basis of their well-equipped physical fitness facilities. University employees were randomly stratified according to their, age, gender, type of university and designation (non-teaching, teaching and management staff), while respondents in each stratum were selected using systematic random sampling technique. Data was collected using a closed-ended questionnaire which was administered to respondents in both universities. The employees’ level of participation in PA was summarised using descriptive statistics. Mann–Whitney U and Kruskal Wallis tests were used to analyse differences in percentages of maximum possible scores with the help of the Statistical Package for Social Sciences (SPSS) version 20.0. It was found that 25% of the employees were physically active while 75% were physically inactive (Mean = 38.20) in relation to use of onsite fitness centres. The most active group were employees below the age of 30 years. Both male and female employees recorded a similar status in participation in PA which was low. There was a significant difference in the status of participation in PA between the two universities (p < .001). This paper recommends that university employees need to take up the opportunity provided by their employers to use the available fitness facilities so as to accumulate the desired daily physical activity amount of at least 30 minutes of moderate to vigorous PA. This is meant to support their physical and mental health needed for their work performance. By the same token, the paper recommends that university administrators should look into strategies that would promote use of onsite fitness centres by the employees so as to increase participation in PA and consequently prevent occurrence of NCDs while promoting productivity at work.